Clinical researchComparison of entropy and bispectral index values during propofol induction - Balci, Canan; Karabekir, H. Selim; Yigit, Muhammet (Archives of Medical Science, 2007)
Introduction: We aimed to identify the entropy levels that would correspond to bispectral index (BIS) levels during general anaesthesia induction in patients who will undergo elective lumbar disc surgery. Material and methods: 30 cases in American Society of Anesthesiology classification groups I-II who underwent lumbar disc surgery under general anaesthesia were included in our study between January 1, 2004, and December 31, 2005. BIS and entropy electrodes were applied at the same time in 30 cases in the study group. Non-invasive mean arterial pressures (NMAP), heart rates (HR) and peripheral oxygen saturation (SpO2) were measured in all cases before induction. During induction, measurements of these parameters every 30 seconds were also recorded. In order to assess the level of sedation during anaesthesia, ‘Observer’s Assessment of Alertness/Sedation’ (OAA/S) scale was used. BIS, entropy and OAA/S values were recorded simultaneously. Results: Induction OAA/S scores were in correlation with BIS and entropy values. Together with the decreases in OAA/S scores, BIS and entropy values decreased as well, but the decrease in entropy values was more rapid. A significant difference was found between BIS and entropy induction values (p<0.05). Induction MAP and HR values at 30, 60, 90, 120 seconds were lower than the values of the control, which was statistically significant (p<0.05). Conclusions: During the induction of general anaesthesia, we found entropy values to be more sensitive and they demonstrated a more rapid decrease than BIS. Based on this observation, induction agents that might cause severe hypotension could be more safely administered under entropy monitoring.